Stable Isotopes in Tree Rings Inferring Physiological, Climatic and Environmental Responses - Siegwolf, Rolf T. W.; Brooks, J. Renée; Roden, John; Saurer, Matthias (Tree Physiology, 2022)
This Open Access volume highlights how tree ring stable isotopes have been used to address a range of environmental issues from paleoclimatology to forest management, and anthropogenic impacts on forest growth. It will further evaluate weaknesses and strengths of isotope applications in tree rings. In contrast to older tree ring studies, which predominantly applied a pure statistical approach this book will focus on physiological mechanisms that influence isotopic signals and reflect environmental impacts. Focusing on connections between physiological responses and drivers of isotope variation will also clarify why environmental impacts are not linearly reflected in isotope ratios and tree ring widths. This volume will be of interest to any researcher and educator who uses tree rings (and other organic matter proxies) to reconstruct paleoclimate as well as to understand contemporary functional processes and anthropogenic influences on native ecosystems. The use of stable isotopes in biogeochemical studies has expanded greatly in recent years, making this volume a valuable resource to a growing and vibrant community of researchers.